A μ‐Phosphido Diiron Dumbbell in Multiple Oxidation States. (23rd August 2019) - Ghosh, Munmun; Cramer, Hanna H.; Dechert, Sebastian; Demeshko, Serhiy; John, Michael; Hansmann, Max M.; Ye, Shengfa; Meyer, Franc
Abstract: The reaction of the ferrous complex [LFe(NCMe)2 ](OTf)2 (1 ), which contains a macrocyclic tetracarbene as ligand (L), with Na(OCP) generates the OCP − ‐ligated complex [LFe(PCO)(CO)]OTf (2 ) together with the dinuclear μ‐phosphido complex [(LFe)2 P](OTf)3 (3 ), which features an unprecedented linear Fe‐(μ‐P)‐Fe motif and a "naked" P‐atom bridge that appears at δ=+1480 ppm in the 31 P NMR spectrum. 3 exhibits rich redox chemistry, and both the singly and doubly oxidized species 4 and 5 could be isolated and fully characterized. X‐ray crystallography, spectroscopic studies, in combination with DFT computations provide a comprehensive electronic structure description and show that the Fe‐(μ‐P)‐Fe core is highly covalent and structurally invariant over the series of oxidation states that are formally described as ranging from Fe III Fe III to Fe IV Fe IV . 3 –5 now add a higher homologue set of complexes to the many systems with Fe‐(μ‐O)‐Fe and Fe‐(μ‐N)‐Fe core structures that are prominent in bioinorganic chemistry and catalysis. Abstract : Die nackte Wahrheit : Durch Nutzung eines makrocyclischen Tetracarben‐Ligandengerüsts und Na(OCP) als P‐Atomtransferreagenz konnte ein Dieisenkomplex mit einer „nackten" P‐Brücke isoliert werden. Der Komplex zeigt eine vielseitige Redoxchemie, und sowohl die einfach als auch die zweifach oxidierte Spezies konnten isoliert und charakterisiert werden. Der lineare Fe‐(μ‐P)‐Fe‐Kern ist hoch kovalent und strukturell unverändert über drei Oxidationsstufen.